A trusted online donation platform: crowdfunding by utilizing network of mosque (NoM) - Ahmad Dahlan, Abdul Rahman; Abdul Razak, Sitti Munirah; Omar, Emmy Rosyida; Jabridin, Faran Nina; Kumala, Rahmi (IRPN Publishers, 2016)
This paper proposes a platform that use crowdfunding by utilizing network of mosque. The development of this platform is aim to improve the charity activities globally as well as to give the ability to donate through a more trusted and secured channel. By understanding the demand to make the donation or charitable causes on current day society, it is shown that crowdfunding platform is one of the solution for it. In order to discover more into the importance of this platform the quantitative methodology was used via online questionnaire which was distributed to four customer segments namely donor, needy people, startup business and advertiser. Also the findings were also used for value proposition design and followed by business model canvas. The main finding of this study indicates that most the respondents are interested with the idea of crowdfunding which can further prove that they are ready to utilize such facilities to do or gain donation. Therefore, findings showed that the proposed solution can be used to accommodate with current issues which was meant to be solved.